The Role of Renewable Energy Consumption and FDI in Testing the Existing of Environmental Kuznets Curve in Vietnam - Nguyen, Thuan; Dang, Bac Hai; Tran, Thi Diem Nga; Su, Thi Oanh Hoa (International Journal of Energy Economics and Policy, 2020)
This study tests the environmental Kuznets curve while examining the role of renewable energy sources and FDI to potentially effect the amount of CO2 emissions in Vietnam. Using Autoregressive Distributed Lag (ARDL) approach, the relationship between CO2 emissions and GDP, FDI and sources of energy consumption has been investigated during 1980–2018 in Vietnam. The results of study reveal that there is non-existence EKC for Vietnam in long run and a sign of inverted U- shape in short run in this period. The analysis also shows that the coefficient of energy consumption from hydro-power renewable sources which correlates to CO2 emissions is negative and significant while FDI leads to increasing carbon dioxide emissions in the long run. That implies Vietnam could have been benefited from a drop in CO2 emissions at some point in the early stage of the period, however, the country has been facing environmental pollution increase as GDP and FDI growth. Keywords: Environmental Kuznets Curve, Renewable energy, FDI, Vietnam. JEL Classifications: O44, Q56, Q4 DOI: https://doi.org/10.32479/ijeep.10367